Asociación entre semanas de inmovilización de muñeca y discapacidad del hombro. Papel del catastrofismo y la kinesiofobia como confudidores. - Cantero-Téllez, Raquel (My University, 2024)
The purpose of this study was to assess the association between wrist immobilization after injury and the development of shoulder disability and to explain the influence of psychological factors as confounders. Design: Cross-sectional Study Participants: Adults over 18th wrist and thumb immobilization up to 2/3 proximal to the forearm after a distal radius fracture or Scaphoid fracture who met the established inclusion criteria were included in the study. Intervention: One hundred and eighteen (n=118) participants with wrist-hand immobilization resulting from distal radius or scaphoid fractures. Participants completed self-reported questionnaires encompassing psychosocial factors, pain, and functional limitations. Demographic, clinical and surgical data were obtained from the medical records of participants. Outcomes measures: The primary outcome of the study was “Shoulder pain and disability questionnaire score” (SPADI). The exposure variable was “Time of immobilization in weeks” (Inmob_Week). The independent variables were: ‘Age’, ‘Gender’, ‘Injury’, Tampa Scale for Kinesiophobia (TSK), Pain Catastrophizing Scale (PCS) , Numerical rating Scale (NRS).Fifteen multivariate regression models were scrutinized for potential confounding. Results: Interactions between the exposure (Inmob_Week) and potential confounders were not significant (p=0.374). The most robust adjusted model, demonstrated that type of injury, kinesiophobia and pain intensity were confounders in the association between immobilization duration and shoulder pain/disability. Conclusion: For each week that we increased wrist immobilization, the shoulder pain/disability score increased by 1.38 (95% CI: 0.55 to 2.21), being the original type of injury, catastrophizing, and pain variables confounders of the effect.
Keywords: Hombros - Lesiones y heridas; Manos - Lesiones y heridas; Dolor - Aspectos psicológicos; Immobilization; Pain; Shoulder; Wrist; Disability; Psychological factors